ANALOGY OF EXHIBITS OF KĖDAINIAI REGIONAL MUSEUM WITH OBJECTS IN LATVIA AND BELARUS : COMPARISON OF WOODEN PLATES - Banys, Vaidas (Via Latgalica, 2014)
Plates in household of wealthy Europeans appeared only in the Early Modern Era, and among mostly people plates became a necessary tool only from the second half of the 19th century. New culture of eating using personal dishes was taken even earlier by manors and cities, meanwhile peasants considered it as unnecessary costs, that cannot supplant a personal dipper and slice of bread by a common table. In some European regions peasants used wooden dishes, that later were substituted by ceramic ones.